2022
DOI: 10.1108/itp-06-2021-0423
|View full text |Cite
|
Sign up to set email alerts
|

VR tourism experiences and tourist behavior intention in COVID-19: an experience economy and mood management perspective

Abstract: PurposeVirtual reality (VR) technology is a potential tool for tourism marketers to maintain the attractiveness of their destinations and recover from the COVID-19 pandemic. However, the effectiveness of VR technology in motivating potential tourists' visit intention under lockdown conditions remains unknown. An integrated model based on the experience economy framework and mood management theory was, therefore, used to explain how tourists' VR experiences affect their mood management processes and subsequent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 117 publications
2
12
0
1
Order By: Relevance
“…With the advantages of security and convenient experiences, virtual tourism can help tourists realize their desire to travel and thus satisfy their needs. In addition, prolonged social distancing and lockdowns may cause psychological problems (Leung et al , 2022). By providing pleasant travel experiences, virtual tourism can meet their psychological demands for leisure and relaxation.…”
Section: Discussionmentioning
confidence: 99%
“…With the advantages of security and convenient experiences, virtual tourism can help tourists realize their desire to travel and thus satisfy their needs. In addition, prolonged social distancing and lockdowns may cause psychological problems (Leung et al , 2022). By providing pleasant travel experiences, virtual tourism can meet their psychological demands for leisure and relaxation.…”
Section: Discussionmentioning
confidence: 99%
“…As the objective of this study is to identify key predictors of travelers' external search behaviors and impulse buying in a theoretical framework with a large number of constructs, PLS‐SEM is appropriate for this study. As such, we follow recent marketing studies (e.g., Cheung et al, 2022; Leung et al, 2023; Sharipudin et al, 2023) with similar objectives to adopt PLS‐SEM to analyze the data.…”
Section: Methodsmentioning
confidence: 99%
“…The study confirmed the hypotheses, with significance tested by evaluating each route and the model fit of the structural equation model (Hair Jr. et al, 2009). (Huang, 2023;Leung et al, 2023). With regards to income, the largest group (22.38%) reported an income above ¥6001, followed by those earning between ¥3001 and ¥4000 (21.34%).…”
Section: Data Collection and Analysismentioning
confidence: 99%